2017
DOI: 10.1073/pnas.1706193114
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9–based treatment of myocilin-associated glaucoma

Abstract: Primary open-angle glaucoma (POAG) is a leading cause of irreversible vision loss worldwide, with elevated intraocular pressure (IOP) a major risk factor. Myocilin (MYOC) dominant gain-offunction mutations have been reported in ∼4% of POAG cases. MYOC mutations result in protein misfolding, leading to endoplasmic reticulum (ER) stress in the trabecular meshwork (TM), the tissue that regulates IOP. We use CRISPR-Cas9-mediated genome editing in cultured human TM cells and in a MYOC mouse model of POAG to knock d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(110 citation statements)
references
References 45 publications
2
105
0
3
Order By: Relevance
“…Adenovirus encoding parts of the CRISPR/Cas9 system have been used to target the myocilin mutations in a murine model and it was found that by targeting the myocilin mutation, the IOP decreased in affected mice and this prevented further damage to the rodent eyes. The same laboratory also looked at the effects of the vector on the trabecular network of ex vivo eyes and reported a decrease in myocilin mRNA . These reports open avenues for translation into clinical trials of early‐onset glaucoma caused by myocilin mutations.…”
Section: Future Directions To Increase Efficacy Of Therapymentioning
confidence: 96%
See 3 more Smart Citations
“…Adenovirus encoding parts of the CRISPR/Cas9 system have been used to target the myocilin mutations in a murine model and it was found that by targeting the myocilin mutation, the IOP decreased in affected mice and this prevented further damage to the rodent eyes. The same laboratory also looked at the effects of the vector on the trabecular network of ex vivo eyes and reported a decrease in myocilin mRNA . These reports open avenues for translation into clinical trials of early‐onset glaucoma caused by myocilin mutations.…”
Section: Future Directions To Increase Efficacy Of Therapymentioning
confidence: 96%
“…The same laboratory also looked at the effects of the vector on the trabecular network of ex vivo eyes and reported a decrease in myocilin mRNA. 139 These reports open avenues for translation into clinical trials of early-onset glaucoma caused by myocilin mutations.…”
Section: Glaucomamentioning
confidence: 99%
See 2 more Smart Citations
“…Only until recently, two significant mouse models have been established for studies of TM cell therapies. 83,84 Zhu et al reported that aqueous humour out-flow was restored following transplantation of iPSC-derived TM cells in a transgenic mouse model of glaucoma. 84 Their results suggest that transplantation of iPSC-TM may restore out-flow facility and IOP in aged mice.…”
Section: Current S Tatus Of Cell Ther Apy In Animal or Clini C Al Smentioning
confidence: 99%